Feasibility of alum sludge as phosphate removal - Nazirul M.Z.; Hua C.K.; Sidek L.M. (Trans Tech Publications Ltd, 2023)
Alum sludge contained a large portion amount of the aluminum derived from the coagulation process in secondary stage water treatment. Alum sludge is discharge to the landfill and it can affect on disposal management. This study investigates the treatment of wastewater using the low-cost adsorption material and also an innovation in green technology for the preservation of the environment. This finding attempts to determine the effectiveness of dewatered water treatment alum sludge as media to remove pollutant (phosphate) from wastewater. The continuous flow test approach with constant speed allocate is being used in this study. Alum sludge was prepared in 2.36 mm sieve size in dry condition and the initial synthetic water concentration (phosphate solution) was set in increasing order 2.6 mg/L to 30.5 mg/L. The test was monitored over 30 days with constant flow rate. The results indicated removal phosphate in beginning of contact time at 30% - 90%. The maximum percentage removal is 91% - 98% in various condition. The dewatered alum sludge from water treatment plant has great potential as phosphate removal. © (2014) Trans Tech Publications, Switzerland.